1995
DOI: 10.1126/science.7809611
|View full text |Cite
|
Sign up to set email alerts
|

A Proficient Enzyme

Abstract: Orotic acid is decarboxylated with a half-time (t1/2) of 78 million years in neutral aqueous solution at room temperature, as indicated by reactions in quartz tubes at elevated temperatures. Spontaneous hydrolysis of phosphodiester bonds, such as those present in the backbone of DNA, proceeds even more slowly at high temperatures, but the heat of activation is less positive, so that dimethyl phosphate is hydrolyzed with a t1/2 of 130,000 years in neutral solution at room temperature. These values extend the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
888
2
18

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 867 publications
(927 citation statements)
references
References 31 publications
19
888
2
18
Order By: Relevance
“…As an example, the rate for the uncatalyzed hydrolysis of dimethyl phosphate at 25 xC (Radzicka & Wolfenden, 1995) has an estimated rate constant of approximately 2r10 x13 s x1 . Further complicating studies of phosphate hydrolysis is the fact that the reaction can not only proceed via P-O cleavage but also via C-O cleavage, which, in this case has been shown to be responsible for up to 99% of the reactivity (and is not the site of cleavage by the relevant enzymes).…”
Section: The Mechanism(s) Of Phosphate Diester Hydrolysismentioning
confidence: 99%
“…As an example, the rate for the uncatalyzed hydrolysis of dimethyl phosphate at 25 xC (Radzicka & Wolfenden, 1995) has an estimated rate constant of approximately 2r10 x13 s x1 . Further complicating studies of phosphate hydrolysis is the fact that the reaction can not only proceed via P-O cleavage but also via C-O cleavage, which, in this case has been shown to be responsible for up to 99% of the reactivity (and is not the site of cleavage by the relevant enzymes).…”
Section: The Mechanism(s) Of Phosphate Diester Hydrolysismentioning
confidence: 99%
“…Although there are now many examples which demonstrate how selective encapsulation in a host cavity can enhance the reactivity of a bound guest, all have failed to reach the degree of increased reactivity typical of enzymes. 4 We now report the catalysis of the Nazarov cyclization by a self-assembled coordination cage, a carbon-carbon bond-forming reaction which proceeds under mild, aqueous conditions. The acceleration in this system is over a million-fold, and represents the first example of supramolecular catalysis that achieves the level of rate enhancement comparable to that observed in several enzymes.…”
mentioning
confidence: 99%
“…Competitive binding experiments between Cp*H and the Diels-Alder adduct (4) showed that 4 is a weaker-binding guest, explaining why it does not noticeably retard the reaction rate.…”
mentioning
confidence: 99%
“…Hydrogen bonding modulates recognition of DNA and RNA bases, and the interaction energy between two bonded complementary nucleobases is dependent on the intrinsic basicity of the acceptor atoms as well as on the acidity of donor NH groups [1,2]. In addition, understanding the intrinsic reactivity of nucleic bases can shed light on key biosynthetic mechanisms in which nucleobases are substrates [3][4][5][6][7][8].…”
mentioning
confidence: 99%